USE OF RECYCLED MATERIALS: UTILIZING RECYCLED MATERIALS IN THE PRODUCTION OF SOLAR PANELS TO REDUCE ENVIRONMENTAL IMPACT AND ENHANCE EFFICIENCY - Abdugafforov Nurbek (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The increasing demand for renewable energy sources has driven the need for more sustainable production methods. This article explores the use of recycled materials in the production of solar panels, highlighting the potential to reduce environmental impact and enhance the efficiency of solar energy systems. It examines the types of recycled materials that can be utilized, the benefits and challenges of using recycled components, and the future prospects of this approach in the solar industry.